Makna Sumbu Imajiner Yogyakarta Dalam Perspektif Architecture Landscape - Sandi Adji Pratama (Journal of Engineering and Applied Technology, 2025)
The Imaginary Axis of Yogyakarta is a conceptual line that connects Mount Merapi, the Yogyakarta Palace, and the Southern Sea, which carries philosophical, cultural, and ecological values in shaping the urban space. This study aims to examine the meaning of the imaginary axis from the perspective of landscape architecture, focusing on the relationship between natural elements, urban spatial planning, and Javanese cultural symbolism. The methods used include literature review, spatial analysis, and a descriptive qualitative approach to urban landscape morphology. The research results indicate that the imaginary axis is not merely an urban planning orientation, but also a representation of Javanese cosmological harmony that integrates humans, nature, and spirituality. From the perspective of landscape architecture, this axis demonstrates visual, ecological, and philosophical connectivity that creates Yogyakarta's landscape identity as a cultural city. Thus, the imaginary axis holds deep significance for spatial balance, the value of local wisdom, and provides inspiration for the development of sustainable architecture and landscapes in the future.